Ayurveda – the classical indian medicine. - Deveza, Antonio Cesar Ribeiro Silva (Revista de Medicina, 2013)
The aim of this article is to introduce briefly the foundations of the Classical Indian Medicine, Ayurveda. The Sanskrit word Ayurveda literally means the knowledge (veda) of longevity (ayus). We present a history on the main influences of other ancient medicines that coexisted with Ayurveda, due to the several invasions that the Indian Territory suffered throughout all of its history. Ayurveda has an experimental character and a refined observation of symptoms and signs of diseases, distinct from other forms of mystic medicines practiced within the Indian Territory by orthodox Brahmins priests. The fundamental principles of Ayurveda go from the Samkhya Philosophy that offers its metaphysical bases, through the three humours (tridosha vidya) and five basic elements doctrines, the pathophysiology with the description of the numerous evolutionary steps of diseases and prognosis according to functionality of the seven basic body tissues, in both their healthy and pathological forms. Likewise, we describe the channels of circulation (srotamsi) with their respective  functions of conducting dense materials such as blood, perspiration, feces and urine, as well as the subtle energy channels, responsible for the conduction of thoughts and mental functions. The diagnostic techniques are also presented, along with the various possible forms of treatment, based in mind-body therapies as yoga and meditation practices.